Association of abdominal aortic calcification estimated by plain radiography with outcomes in haemodialysis patients: A 6‐year follow‐up study. Issue 7 (30th August 2019) - Zhu, Xuying; Cai, Hong; Zhu, Minxia; Zhan, Yaping; Che, Miaolin; Lin, Xinghui; Zhang, Weiming; Ni, Zhaohui
ABSTRACT: Aim: Vascular calcification has played a vital role in increasing the prevalence of cardiovascular disease (CVD) and mortality in maintenance haemodialysis (MHD) patients. This study is aimed at exploring the prognostic value of abdominal aortic calcification (AAC) estimated by plain lateral abdominal radiography in MHD patients. Methods: Lateral abdominal radiography was used to determine the abdominal aortic calcification score (AACS). The serum level of fibroblast growth factor‐23 was tested by enzyme‐linked immunosorbent assay. Patients were divided into two groups: no or minor calcification group (AACS < 5) and moderate to severe calcification group (AACS ≥ 5). All patients were followed up to death or the end of the study (30 November 2016). Results: A total of 114 patients were enrolled in this study, including 64 males (56.1%), and the mean age was 57.42 ± 13.48 years. Seventy‐six patients (66.7%) exhibited AAC. Independent predictors for moderate to severe calcification were older age (odds ratio (OR) 1.06 (1.02–1.10), P = 0.003), longer dialysis vintage (OR 1.01 (1.00–1.02), P = 0.039), presence of smoking (OR 3.01 (1.18–7.70), P = 0.021) and higher Log fibroblast growth factor‐23 serum levels (OR 2.83 (1.01–7.94), P = 0.048). During a median follow‐up of 6.0 (5.6, 6.1) years, 22 patients (19.3%) died of all‐cause death, and 17 cases (14.9%) died of CVD. Kaplan–Meier survival curves showed that patients in the moderate to severe calcification group had significantly higher all‐cause (28.3 vs 11.5%, P = 0.028) and CVD mortality (22.6 vs 8.2%, P = 0.035) than that in the no or minor calcification group. A multivariate Cox regression showed that AACS (hazard ratio 1.08 (1.01–1.15), P = 0.022) was an independent predictor of CVD mortality. Compared with the no or minor calcification group, the risk of CVD mortality was increased by a factor of 3.14 in patients in the moderate to severe calcification group (hazard ratio 3.14 (1.04–9.44), P = 0.042). Conclusion: Our data suggest that AAC is prevalent in MHD patients and could provide potential predictive information for CVD mortality. Plain lateral abdominal radiography, which is simple and cheap and involves lower radiation, might represent an appropriate screening method for evaluating vascular calcification in daily clinical practice. SUMMARY AT A GLANCE: This single‐centre study found that older age, dialysis vintage, smoking and fibroblast growth factor‐23 were predictors of abdominal aortic calcification on lateral abdominal radiography in a cohort of 114 prevalent dialysis patients. The study also identified abdominal aortic calcification as an independent predictor of cardiovascular mortality. The findings show that radiography as a non‐invasive and simple tool could add to the identification of more vulnerable dialysis patients.